Translanguaging and Literacies - García, Ofelia; Kleifgen, Jo Anne (Reading research quarterly, 2020)
The authors trace the development of the concept of translanguaging, focusing on its relation to literacies. The authors describe its connection to literacy studies, with particular attention to bi/multilingual reading and writing. Then, the authors present the development of translanguaging as a sociolinguistic theory, discuss its formulations, and describe what is unique about translanguaging: its beginnings and grounding in educational practice and attention to the performances of multilinguals. The authors argue that multilingualism and bi/multiliteracies cannot be fully understood as simply the use of separate conventionally named languages or separate modes. Instead, translanguaging in literacies focuses on the actions of multilingual readers and writers, which go beyond traditional understandings of language, literacy, and other concepts, such as bi/multilingualism and bi/multilingual literacy. The authors show how multilinguals do language and literacy and how they do so in school. The authors review case studies that demonstrate how a translanguaging literacies framework is used to deepen multilingual students’ understandings of texts, generate students’ more diverse texts, develop students’ sense of confianza (confidence) in performing literacies, and foster critical metalinguistic awareness. The authors end by discussing implications for literacy pedagogy, as well as literacy research, that centers multilingual students.